Riofrío, J.C. (2008). El derecho de los secretos. Bogotá: Temis - Luz Helena Guamanzara Torres (Ius Humani. Jornal do direito, 2010)
This paper provides a review of the book The Law of Secrets, of the author Juan Carlos Martínez-Villalba Riofrío studying the secrets and how law does protect. To this end, the author has analyzed the general theory of secrecy, secrets and methodology, its overall rating, essential elements and their different legal dimensions, the secret as a subjective right. It also establishes that professional secrecy is protected by constitutional principles such as the right to privacy.